Impact of maternal obesity on pregnancy course and maternal and perinatal complications - Lacković, Milan (Medicinski podmladak, 2020)
The prevalence of obesity and obesity-related health problems is increasing worldwide, especially among woman and man of reproductive age and obesity is designated as one of the most important global health threats in 21st century.  Pregnancy in obese woman is considered as a high-risk pregnancy. Pre-pregnancy obesity and excessive gestational weight gain (GWG) are distinct risk factors with differing associated adverse outcomes, but they could also carry a cumulative negative impact on pregnancy course. Pre-pregnancy obesity is the anthropometric parameter most strongly correlated with perinatal complications. Maternal complications following obesity include antepartum, intrapartum and postpartum complications, such as pregnancy related hypertension, preeclampsia, gestational diabetes mellitus, preterm birth, venous thromboembolism, labor dystocia, labor induction, instrumental and cesarean delivery. Fetal complications related to maternal obesity might include increased prevalence of congenital anomalies, growth abnormalities, prematurity and stillbirth. Pre- pregnancy overweight and obesity is a potentially modifiable risk factor compromising pregnancy outcome. Among all complications that might arise during pregnancy and that could not be predicted and therefore prevented, pre- pregnancy overweight and obesity management control can significantly reduce potential pregnancy complications. Pre-conceptual counseling should provide in a timely manner awareness of this arising medical condition and provide risk reduction of complications following pre- pregnancy obesity and excessive GWG obesity, pre-pregnancy obesity, excessive gestational weight gain, pregnancy risk factors, pregnancy complications
Keywords: obesity, pre-pregnancy obesity, excessive gestational weight gain, pregnancy risk factors, pregnancy complications